2012
DOI: 10.1021/jp208855u
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble and Single-Molecule Spectroscopic Study on Excitation Energy Transfer Processes in 1,3-Phenylene-Linked Perylenebisimide Oligomers

Abstract: 1,3-Phenylene-bridged perylenebisimide dimer (PBI2) and trimer (PBI3) were prepared along with monomer reference (PBI1) using perylene imide-anhydride 5 as a key precursor. 3,3-Dimethylbut-1-yl substituents were introduced at the 2,5-positions of perylenebisimide (PBI) to improve the solubilities of PBI oligomers. Actually, no serious aggregation of PBI2 and PBI3 was detected in their dilute CH(2)Cl(2) solutions. Under these conditions, intramolecular electronic interactions among PBI chromophores have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 84 publications
1
32
0
Order By: Relevance
“…in which τ dep is the depolarization time, which is experimentally obtained from the TAA decay profiles 29. As the two PBI units in F2 are identical, it follows that the EET time is twice that of depolarization (Table 3), thus giving rise to EET times of 1.76±0.06 ps (CHCl 3 ) and 0.95±0.06 ps (THF), respectively (Table 4).…”
Section: Discussionmentioning
confidence: 95%
“…in which τ dep is the depolarization time, which is experimentally obtained from the TAA decay profiles 29. As the two PBI units in F2 are identical, it follows that the EET time is twice that of depolarization (Table 3), thus giving rise to EET times of 1.76±0.06 ps (CHCl 3 ) and 0.95±0.06 ps (THF), respectively (Table 4).…”
Section: Discussionmentioning
confidence: 95%
“…In addition to porphyrin, other dyes with strong absorption in the visible have been used to create dimers as, for example, derivatives of perylene (bis)imids (PBI) 2125. H‐type PBI dimers create long‐lived excimer‐like states upon photoexcitation, the fluorescence of which is red shifted compared to the monomer 21.…”
Section: Introductionmentioning
confidence: 99%
“…22 In contrast, J‐type PBI dimers and trimers, which show a redshift in the absorption spectrum and have been investigated through single‐molecule fluorescence experiments, revealed that the lifetime of the delocalized exciton is shorter when it is shared between more monomers 2324. If a phenyl ring was used to link the PBI derivatives, J‐type dimers and trimers were obtained with a lifetime only slightly affected by dimerization and by the presence of Förster‐type energy transfer between the constituting units 25…”
Section: Introductionmentioning
confidence: 99%
“…Thus, assembly measurements, such as ultrafast time-resolved spectral measurements,a re also important to determine the delocalization of the excitation;h owever,t his methodr equires at ime resolution that is greater than 100 fs. [18][19][20][21][22] In this work, we report the fluorescence excitation and fluorescence excitation anisotropy spectra of three multibranched push-pull molecules in apolymer matrix to probe the intramolecular redistribution of the excitation energy among the multibranched chromophores. Our results directly reflect the interplay between the chromophores, and hence,a llow the excita-tion localization/delocalization in multibranched chromophores to be determined.…”
Section: Introductionmentioning
confidence: 99%